PHYTOREMEDIATION OF FISH POND EFFLUENT IN CONSTRUCTED WETLAND USING THREE AQUATIC MACROPHYTES: WATER LETTUCE, DUCKWEED, AND WATER HYACINTH - HORSFALL, J. D; HART, A. I.; ORIAKPONO, E. (Nigerian Journal of Fisheries, 2020)
Fish pond wastewater (effluent) was collected from World Bank SEEFOR empowered fish farm in Umuoko Aluu, Ikwerre Local Government Area (21o55’ 46”S and 47o22’ 24”W) Rivers State, for a period of four weeks. Within the first two weeks of the 28 days subjection of the macrophytes: water hyacinth (Eichhornia crassipes), water lettuce (Pistia stratiotes), duckweed (Lemna minor) and control (without plant) to fish pond wastewater (effluent), turbidity was reduced by 21-24.9% by the water lettuce, 13.98-27.98% by duckweed and 22.86 25.71% by water hyacinth. Total dissolved solids (TDS) were removed at 4.75 – 5.06% by water lettuce, 1.16 – 5.51% by duckweed and 4.48% by water hyacinth. Equally, Nitrate-Nitrogen (Nitrate-N) was reduced at 90.48% by water lettuce and 94.74% by duckweed. Foul smell vanished in all the test plant units within the first week. Duckweed (Lemna minor) was adduced the best in terms of the measured parameters and availability.